Who is going to save us now? Bureaucrats, politicians and risky tasks - Paul A. Raschky; Hannelore Weck-Hannemann (University of Innsbruck, Department of Public Finance, 2007)
The paper compares the policy choices regarding risk-transfer against low-probability-high-loss events between elected and appointed public officials. Empirical evidence using data on U.S. municipality-level shows that appointed city managers are more likely to adopt federal risk-transfer regimes. It is argued that the variation in the level of insurance activity emerges from the different incentive schemes each government form is facing. Controlling for spatial dependencies further shows that the participation decision in the insurance program significantly depends on the decision of neighboring communities.
Keywords: D72; D73; D81; Q54; 330; politicians; bureaucrats; decision making under uncertainty; flood insurance; spatial econometrics; Überschwemmung; Versicherungstechnisches Risiko; Katastrophenhilfe; Entscheidung bei Unsicherheit; Politische Entscheidung; Gemeinde; Schätzung; USA